Resonance Vibration of Railway Bridges Subjected to Passing Vehicles - Moravcik, Milan; Moravcik, Martin (Communications - Scientific letters of the University of Zilina, 2017)
This paper discusses some issues related to dynamic effects in railway bridges focussed on the simulation of the resonant vibration for the small and medium span simply supported railway bridges subjected to a series of moving vehicle. Presented parametric study is concerned with the dynamic deflection of the simply supported railway truss bridge of the span Lb = 38 m, due to the series of the ten moving loads representing a conventional train with the IC-coaches employed in Slovakia, with the impact to the resonance speed c2res = 65.03 m/s = 234.11 km/h. The deflection amplitude (c2 = 33)w(1),(P1,P2....PN)(Lb / 2,t) increase with an increasing number of load forces n = 1, 2, ... N forces moving along the bridge.